Studies in the Gṛhya Prayogas of the Jaiminīya Sāmaveda: 5. Pratisarabandha - Karttunen, Klaus (Studia Orientalia Electronica, 2011)
In the Jaiminīya gṛhya tradition, the pratisarabandha or binding the auspicious string on a man’s or woman’s wrist is given as an auxiliary rite of the sīmantonnayana although in the JSP manuscript, its description is located before the puṁsavana. It has a full chapter in the JSP and (very brief) in the A, which are both edited here, but it is not included on the GKKK. Pratisara or kautuka is an apotropaic string (here consisting of three fibres) that is worn round the wrist or neck. It is mentioned in texts as early as the Kauśikasūtra and several gṛhyasūtras. It is important at weddings, but also used in other ceremonies. It is placed on the right wrist of the yajamāna, but on the left of the woman. The kāppu of Tamils seems to be related.